On Nation and Utopia in Cuadros de costumbres guatemaltecas, by José Milla - Oliva Méndez, María (2017)
The article analyzes the historical and literary meaning of the prose sketches on customs by the Guatemalan José Milla, written to portray a political and ideological proposal developed around the concept of nation. The corpus is divided into two categories of stereotypes (masculine and feminine). That project, concerning the homogenization of the Guatemalan society, is described through literary discourse, as an essential element. Emphasis is given to aspects such as the binomial civilization/barbarism and other related oppositions. This conveys the construction of the utopic idealization of Guatemalan society throughout the 19th century.